The Impact of Implementing the Blue Ocean Strategy on Achieving Competitive Advantage: A Literature Review - Kalangi, Meyti Hanna Ester; Haryono, Haryono (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Blue Ocean Strategy (BOS) offers an innovative approach to achieving competitive advantage by creating new market space (blue ocean) and avoiding direct competition. This literature review explores the impact of implementing BOS on achieving competitive advantage. Studies show a positive relationship between BOS and competitive advantage, with companies that implement BOS experiencing increased market share, profitability, and customer satisfaction. Effective implementation of BOS requires a structured process, including strategic thinking, analysis of customer needs, and alignment of organizational resources. Therefore, further research is recommended to investigate the long-term impact of BOS, its effectiveness in various contexts, and the role of leadership and organizational culture in its implementation. Conclusion Based on the theory, relevant articles and discussions, a hypothesis can be formulated for further research: BOS (X) with the indicators Eliminate, Raise, Reduce and Create has an effect on Competitive Advantage (Y). By implementing BOS, companies can create new value for customers and open up new market space, thereby achieving sustainable competitive advantage. Because the Basic Concept of Blue Ocean Strategy (BOS) is a strategic approach that aims to create new, untapped market space, where competition becomes irrelevant. Furthermore, BOS emphasizes the creation of new value for customers and companies, not just defeating existing competitors